Outcomes of surgery and treatment with selective RET TK inhibitor Selpercatinib in children with MEN2 and advanced MTC. (1st March 2022) - Kurzawinski, Tom; Hubbard, Jonathan; Aziz, Tarek Abdel; Butler, Colin; Gaze, Mark; Brain, Caroline; Marshall, Lynley; Shankar,
Abstract: Background: Patients with MEN2 without family history often present late with advanced MTC. Surgery is not always curative but RET tyrosine kinase pathway is a potential target for molecular treatment for progressive MTC. Methods: Retrospective review of clinical, genetic, biochemical and imaging data of children with MEN2 who developed recurrent and progressive MTC after surgery and were treated with Selpercatinib, a selective RET TK inhibitor. The main parameters were safety, efficacy and objective treatment response. Results: Six children (3M, 3–12years, 4x2B, 2x2A, RET918, 804) presented with palpable lymphadenopathy(5) and elevated calcitonin (median 6560ng/L, 140-46850). Five had metastatic disease on imaging. All had total thyroidectomy with unilateral(2) and bilateral(2) levels 2, 3, 4, 5, 6 lymphadenectomy and resections of JV(1), RLN(2), Vagus(1). Post-operative complications included transient(3) and permanent(1) hypoparathyroidism and Horner's syndrome(2). Two children had second surgery and one EBRT complicated by delayed oesophageal perforation and stridor requiring tracheostomy. None of the children were cured and all had disease progression evidenced by clinical deterioration, rising calcitonin and CEA(3) and worsening radiology(5). All children received Selpercatinib (92mg/m2/dose) orally twice daily. The objective clinical, radiological and biochemical response was 100% with complete resolution of all clinical symptoms (third month) and significant decrease of calcitonin and CEA within 4 weeks. Four had partial radiological response(1–3months). No child had to discontinue Selpercatinib because of a drug toxicity. Median follow up was 13 months(10–20months). Conclusions: Children with MEN2 and advanced MTC can't be cured by surgery and EBRT alone, but Selpercatinib has shown remarkable therapeutic efficacy with clinical, biochemical and radiological improvement and minimal toxicity.